Operative considerations for rectovaginal fistulas - Kniery, Kevin R (World J Gastrointest Surg, 2015)
To describe the etiology, anatomy and pathophysiology of rectovaginal fistulas (RVFs); and to describe a systematic surgical approach to help achieve optimal outcomes. A current review of the literature was performed to identify the most up-to-date techniques and outcomes for repair of RVFs. RVFs present a difficult problem that is frustrating for patients and surgeons alike. Multiple trips to the operating room are generally needed to resolve the fistula, and the recurrence rate approaches 40% when considering all of the surgical options. At present, surgical options range from collagen plugs and endorectal advancement flaps to sphincter repairs or resection with colo-anal reconstruction. There are general principles that will allow the best chance for resolution of the fistula with the least morbidity to the patient. These principles include: resolving the sepsis, identifying the anatomy, starting with least invasive surgical options, and interposing healthy tissue for complex or recurrent fistulas.